2020
DOI: 10.1097/iae.0000000000002747
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Abca4-Related Retinopathy

Abstract: This study underscores the prognostic value of demographic, functional, genetic, and lesion geometry parameters in ABCA4-related retinopathy. Trial design including inclusion criteria based on these factors may provide economic benefits by selection of appropriate participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…31 Müller et al 4 have reported a mean rate of RPE-atrophy enlargement of 0.89 ± 0.13 mm 2 /year in ABCAArelated retinopathy eyes. Whereas both the ProgStar and Müller et al 4 used the mean as a measure of central tendency, it might be not appropriate in our series as the distribution of progression rates was highly rightskewed ( Supplementary Fig. S3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…31 Müller et al 4 have reported a mean rate of RPE-atrophy enlargement of 0.89 ± 0.13 mm 2 /year in ABCAArelated retinopathy eyes. Whereas both the ProgStar and Müller et al 4 used the mean as a measure of central tendency, it might be not appropriate in our series as the distribution of progression rates was highly rightskewed ( Supplementary Fig. S3).…”
Section: Discussionmentioning
confidence: 97%
“…30,31 A second model was carried out in which the squareroot-transformed RPE atrophy enlargement rate was the dependent variable. 4 Because baseline SW-FAF and NIR-FAF hypoautofluorescent areas strongly correlated with each other, only the former was included in multivariable models to avoid collinearity. Complete case analysis was used to deal with missing data in all the models.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a generally increased fundus autofluorescence (AF) intensity followed by distinct patterns of increased and decreased AF as well as thinning of retinal layers in the optic coherence tomography (OCT) associated with loss of function [3][4][5]. However, the clinical presentation and individual progression rate are highly variable [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the view of emerging interventional clinical trials, the ability to identify patients by rate of expected disease progression would be advantageous in order to maximize the potential of an intervention to demonstrate therapeutic effectiveness and improve the efficiency of future trials [7]. Several morphological and functional classifications have been proposed previously [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation